A historical and palaeopathological perspective on cancer - Galassi, F.M.; Varotto, E.; Vaccarezza, Mauro; Martini, M.; Papa, V. (2024)
Cancer is often wrongly considered to be a modern disease in many popular medical venues. Cancers have been known to mankind since ancient times. In fact, its antiquity can be proved through the application of palaeopathological methodologies. The present perspective piece demonstrates by means of a historical and palaeopathological analysis how oncological manifestations were present long before the emergence anatomically modern humans and addresses the epidemiological transition from ancient times to the contemporary world.